Development of ergonomic-axiomatic design parameters for virtual environment / Hartomo - Hartomo, - (2013)
Ergonomic design of virtual environment will enhance the effectiveness of communication between the users and the virtual world, as well as avoiding the unwanted side effects, especially those affecting vision. Thus, it is highly essential to ensure that a set of design parameters of virtual environment should satisfy the ergonomic requirements and the user’s criteria. The objective of this study is to develop the ergonomic design parameters to design the virtual environment and to propose the methodology to invent ergonomic design parameters. Axiomatic design method is applied to map the physical domain that satisfies the functional domain and the functional domain that satisfies the customer domain. This process should be referred to the independence axiom. The implementation of ergonomic concept is considered as a basis of mapping process to develop the design parameters of virtual environment and the methodology proposed. “Fitting the task to the man” is the main principle in ergonomic design. Survey by using questionnaire was conducted to identify the customer’s criteria and investigate the visual disorder on the users. A field study was completed to obtain the criteria needed by the customer in the virtual environment. Meanwhile, an experimental study was done as the empirical evidence on visual symptoms experienced by user’s vision when interacting with the virtual environment. Thus, virtual robot manufacturing system, as the case study, was developed as virtual stimulus by using Direct X and C# programming. Also, Autodesk 3 DS Max software was used to build the virtual objects. This experimental study was divided into two activities. The first was to investigate the ergonomic attributes and the second was for validation.